1958
DOI: 10.1677/joe.0.0170107
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Sex Hormones on the Adrenal Gland of the Male Rat

Abstract: Oestradiol dipropionate enhances the effect of both endogenous and exogenous adrenocorticotrophic hormone (ACTH) on the weight of the adrenal glands of the male rat. Methyl testosterone has the opposite effect. It is concluded that sex hormones exert their effect by modifying both hypophysial secretion of ACTH and adrenocortical sensitivity to ACTH.The adrenal glands, which in most mammalian species are larger in the adult female than in the adult male, decrease in size after ovariectomy and increase after orc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1960
1960
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…In the androgenized female rats the CR-activity was similar to that in the males. The reason for these differences in hypothalamic CR-activity is not readily apparent; however, a number of results suggest that there may be sex differences in the activity of the hypothalamic-pituitary-adrenal system (Gemzell, 1952;Gompertz, 1958;Halberg & Haus, 1960;Kitay, 1961;Critchlow, Liebelt, Bar-Sela, Mountcastle & Lipscomb, 1963).The CRactivity of brain cortical tissue extract has been discussed by Chiappa & Fink (1977).…”
Section: Discussionmentioning
confidence: 99%
“…In the androgenized female rats the CR-activity was similar to that in the males. The reason for these differences in hypothalamic CR-activity is not readily apparent; however, a number of results suggest that there may be sex differences in the activity of the hypothalamic-pituitary-adrenal system (Gemzell, 1952;Gompertz, 1958;Halberg & Haus, 1960;Kitay, 1961;Critchlow, Liebelt, Bar-Sela, Mountcastle & Lipscomb, 1963).The CRactivity of brain cortical tissue extract has been discussed by Chiappa & Fink (1977).…”
Section: Discussionmentioning
confidence: 99%
“…Sex differences in HPA regulation in the rodent arise from both neuronal imprinting during early development and distinct actions of estradiol (E 2 ) and testosterone (Te) in adulthood. 9397 In the young adult animal, exposure to E 2 typically potentiates stress-induced ACTH secretion by: (1) attenuating negative feedback in the hypothalamus, hippocampus, amygdala, and pituitary gland 98,99 ; (2) inducing AVP, CRH, and CRH-R1 gene expression in the paraventricular nucleus (PVN) 77,93,100103 ; (3) enhancing adrenal responsiveness to ACTH 104107 ; (4) muting hippocampal and bed nucleus of the stria terminalis–directed inhibition of PVN neurons 108 ; and (5) blunting homologous downregulation of limbic GR. 76 Conversely, Te and 5α-dihydrotestosterone (5α-DHT) generally exert opposing effects on the fore-going mechanisms, resulting in diminished stress-stimulated ACTH secretion (see Fig.…”
Section: Experimental Insights Into and Clinical Inferences Regardingmentioning
confidence: 99%
“…Moreover, Gemzell has reported increased secretion of ACTH in male rats following administration of estradiol [68]. The authors suggested that estradiol affects both the hypophysial secretion of ACTH and adrenal cortical sensitivity to ACTH based upon adrenal weight changes in intact and castrated rats [69].…”
Section: Gender Differences In Hpa-axis Reactivitymentioning
confidence: 99%